The effect of the disposition of coordinated oxygen atoms on the magnitude of the energy barrier for magnetization reversal in a family of linear trinuclear Zn–Dy–Zn complexes with a square-antiprism DyO8 coordination sphere. Issue 13 (10th March 2017) - Oyarzabal, Itziar; Rodríguez-Diéguez, Antonio; Barquín, Montserrat; Seco, José M.; Colacio, Enrique
Abstract : A family of linear trinuclear Zn–Dy–Zn complexes with SIM behaviour and high thermal energy barriers has been prepared. Abstract : A series of trimetallic Zn–Dy–Zn complexes of the general formula [ZnX(μ-L)Dy(μ-L)XZn]Y· n S, where H2 L is the compartmental ligand N, N ′-dimethyl- N, N ′-bis(2-hydroxy-3-formyl-5-bromobenzyl)ethylenediamine, X is the coligand (X = Cl, Br, I and N3 ), Y is the counteranion and S are the crystallization solvent molecules have been synthesized and magnetically characterized. In all these complexes, the Dy(iii ) ions exhibit DyO8 coordination environments with a slightly distorted square-antiprism D 4d symmetry. Due to the disposition of the oxygen atoms around the Dy(iii ) ions, large easy-axis anisotropy is expected, which is responsible for the high thermal energy barriers for the reversal of the magnetization observed at zero field (in the 144–170 K range for all complexes). A preliminary correlation between the disposition of the oxygen atoms of the ligand (phenoxo and aldehyde) in the DyO8 coordination sphere and the value of U eff has been established.